Aplikasi Pembuatan Form Ekspor Pajak Berbasis Web Di PT. XYZ - Zen Munawar; Dadang Sudrajat; Rudi Kurniawan; Ajudin; Novianti Indah Putri (Prosiding SISFOTEK, 2023)
PT. XYZ Indonesia is a subsidiary of M Inc which operates in the fashion doll sector which produces children's toys such as Barbie dolls and Hot Wheels toy cars. This company still uses Microsoft Excel to create Tax Export Forms, but this system still has weaknesses because it takes a long time and is less efficient. The aim of this research is to determine system constraints and the solutions needed to overcome these constraints. The research was conducted using the SDLC or Software Development Life Cycle methodology with a waterfall model. The data collection techniques used were literature studies, field studies and interviews. The result of the research carried out is the design of a Web-Based Export Tax Form application using the Asp.Net MVC framework. With this system it is hoped that it can improve the performance of Finance staff.